2015
DOI: 10.1002/dvdy.24271
|View full text |Cite
|
Sign up to set email alerts
|

Fate mapping of ptf1a‐expressing cells during pancreatic organogenesis and regeneration in zebrafish

Abstract: Background Pancreas development in zebrafish shares many features with mammals, including the participation of epithelial progenitor cells expressing pancreas transcription factor 1a (ptf1a). However, to date it has remained unclear whether, as in mammals, ptf1a-expressing zebrafish pancreatic progenitors are able to contribute to multiple exocrine and endocrine lineages. To delineate the lineage potential of ptf1a-expressing cells, we generated ptf1a:creERT2 transgenic fish and performed genetic-inducible lin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
22
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(24 citation statements)
references
References 46 publications
2
22
0
Order By: Relevance
“…4N, inset); suggesting that these are the equivalent of mammalian multipotent pancreatic progenitor cells. This interpretation is concordant with ptf1a lineage tracing studies in zebrafish (Wang et al, 2015). We next asked how loss of insulin affected development of this progenitor domain in our model.…”
Section: Resultssupporting
confidence: 88%
See 1 more Smart Citation
“…4N, inset); suggesting that these are the equivalent of mammalian multipotent pancreatic progenitor cells. This interpretation is concordant with ptf1a lineage tracing studies in zebrafish (Wang et al, 2015). We next asked how loss of insulin affected development of this progenitor domain in our model.…”
Section: Resultssupporting
confidence: 88%
“…The failure of β cell compensation to meet insulin demand results in diabetes mellitus, a metabolic disease of insufficient insulin signaling that is characterized by uncontrolled hyperglycemia and its associated morbid complications. While compensation can be transiently mediated in part via increased insulin production and release from existing β cells, long term β cell compensation involves the expansion of β cell mass by multiple mechanisms (Asghar et al, 2006; Wang et al, 2015; Weir and Bonner-Weir, 2004). For instance, in mice physiological stresses like over-nutrition and pregnancy can accelerate β cell replication (Kim et al, 2010; Lee and Nielsen, 2009; Tanaka and Wands, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…Embryos were staged by hpf at 28.5°C (Kimmel et al, 1995). The following lines were used: Tg(fabp10a: EGFP) as3 (Her, Yeh, and Wu, 2003), Tg(ins:Kaede) jh6 (Pisharath et al, 2007), Tg(ins:dsRed) m1018 (Shin et al, 2008), Tg(ins:Hsa.HIST1H2BJ-GFP;ins:DsRed) s960 (Ninov et al, 2013) abbreviated Tg(ins:H2B-GFP;ins: DsRed), Tg( pck1:Luciferase) s952 (Gut et al, 2013), Tg BAC (neuroD: EGFP) nl1 (Obholzer et al, 2008), pdx1 sa280 (Kimmel et al, 2015), insulin bns102 (Mullapudi et al, 2018), Tg(insulin:loxP:mCherrySTOP: loxP:H2B-GFP; cryaa:Cerulean) s934 (Hesselson et al, 2011), Tg(sox17: GFP) s870 (Sakaguchi et al, 2006), Tg(Tp1bglob:H2BmCherry) S939 (Ninov et al, 2012), Tg(ubb:loxP:CFP:loxP:H2B-mCherry) jh63 (Wang et al, 2015), Tg BAC (arxa:Cre) bns250 (this study), Tg BAC ( pdx1:EGFP) bns13 (this study), Tg BAC ( pdx1:luciferase2) bns17 (this study) and Tg(ins:loxP-Eco.NfsB-mCherry-loxP-luciferase) bns152 abbreviated as Tg(ins:mCherry) (this study).…”
Section: Zebrafish Husbandry and Strainsmentioning
confidence: 99%
“…Ventral bud cells in zebrafish are similar to mouse MPCs in terms of cellular events and molecular pathways (Figure 1b,c). The zebrafish ventral bud contains two cell populations: Notch-Off, Ptf1a positive cells that give rise to the exocrine pancreas (Figure 1b; Ghaye et al, 2015;Parsons et al, 2009;Wang, Park, Parsons, & Leach, 2015), and a Notch-On, Ptf1a negative cell population that differentiates into the ductal system and endocrine cells (Figure 1b; Parsons et al, 2009;Wang, Rovira, Yusuff, & Parsons, 2011;Ghaye et al, 2015). Experiments using some Notch signal reporter lines and notch signal inhibitors revealed that the reduction of Notch signaling in the Notch-On cells triggered their proliferation and differentiation into endocrine cell types (Figure 1b; Matsuda, Parsons, & Leach, 2013;Ninov, Borius, & Stainier, 2012;Parsons et al, 2009), and that continuous Notch-On cells became ductal cells (Figure 1b, Wang et al, 2011).…”
Section: Zeb R Afis H Pan Cre Atic De Velopmentmentioning
confidence: 99%
“…It is unclear how teleost ventral bud has acquired the ability of islets differentiation, because it is unclear what molecular pathways are working in the ventral bud of Lamprey. The zebrafish ventral bud contains two cell populations: Notch-Off, Ptf1a positive cells that give rise to the exocrine pancreas(Figure 1b;Ghaye et al, 2015;Parsons et al, 2009;Wang, Park, Parsons, & Leach, 2015), and a Notch-On, Ptf1a negative cell population that differentiates into the ductal system and endocrine cells(Figure 1b;Parsons et al, 2009;Wang, Rovira, Yusuff, & Parsons, 2011;Ghaye et al, 2015). Furthermore, ptf1a knock down results in a complete loss of acinar cells in Xenopus as in zebrafish ventral bud(Figure 1b;Afelik et al, 2006;Lin et al, 2004;Pearl et al, 2009).…”
mentioning
confidence: 99%